Use of mannans as an elicitor of the defense response on Vitis vinifera against fungi causing Grapevine Trunk Diseases - Alfonso Ortega; José Antonio García; Jerónimo del Moral; Francisco Espinosa; Inmaculada Garrido (PLoS ONE, 2026)
Grapevine Trunk Diseases (GTDs) are caused by phytopathogenic fungi that compromise grapevine productivity and wine quality. Most GTDs preventive treatments are chemical-based and environmentally harmful. One goal of the European Green Deal is to develop sustainable agriculture which does not harm the environment and reduces pesticide use and an alternative to those treatments may be the use of elicitors such as oligosaccharides from fungi. Many studies confirm that oligosaccharides activate the defence response. The experiment was carried out in vineyards of Tempranillo and Airén cvs. Asymptomatic and symptomatic vines were treated with mannans. Leaves and grapes were taken and pigments and phenols content, polyphenol oxidase (PPO) and superoxide dismutase (SOD) activities and gene expression of several defence enzymes were determined. The mannan addition to symptomatic vines was more positive for the leaves than for the grapes, palliating the damage caused by the disease, especially in the cv. Tempranillo. On the one hand, in the leaves, mannans caused an increase in phenols and PPO activity and expression; on the other hand, in grapes, although phenols increased, the other parameters did not. Mannans increased the expression levels of chalcone synthase ( CHS1 , CHS3 ), phenylalanine ammonia lyase ( PAL ), SOD , and PPO in asymptomatic leaves of both cultivars. In symptomatic leaves, CHS3 and PAL expression decreased in both cultivars, while CHS1 and PPO increased only in Tempranillo. In grapes, the expression of the genes varied due to the development of the disease. The mannan treatment seemed to reduce the oxidative stress caused by GTDs, but, above all, mannans would act as a biostimulant activaing the defence system of asymptomatic vines that would help them respond more successfully to a possible pathogenic fungi infection, that although this response depended on the cultivar.